Disruption to diabetes and hypertension care during the COVID-19 pandemic in Latin America and the Caribbean and mitigation approaches: a scoping review - Ogungbe, Oluwabunmi; Jabakhanji, Samira Barbara; Mehta, Roopa; McCaffrey, John; Byrne, David; Hurley, Sinéad; Rosman, Lori; Bansah, Eyram Cyril; Ibukun, Folahan; Quarshie, Irene Afua; Lord, Katherine; Lu, Yidan; et al. (BMC health services research, 2025)
The COVID-19 pandemic disrupted care for non-communicable diseases globally. This study synthesizes evidence on disruptions to primary care, focusing on hypertension and diabetes care and mitigation approaches taken during the pandemic in Latin America and the Caribbean (LAC).